Splitting techniques in vertical pneumatic conveying - Roberts, Jacob Thomas (2007)
The following work details an investigation into improving efficiency in pulverised-fuel- fired power stations. The particular area of focus is the splitter box; this is located in the pneumatic conveying pipeline within the power station. The conveying pipelines take the pulverised fuel from the mill to the burner face, at some point the air/fuel mixture has to be split to feed the individual burners. It is at these points that the splitter boxes occur, dividing the pipe into multiple legs.